PENGABDIAN MASYARAKAT DI BANJAR ABASAN SINGAPADU: MENGGERAKAN PERUBAHAN UNTUK KESEJAHTERAAN RAKYAT - Ni Putu Era Suandari; Ni Luh Devi Antari; Ni Wayan Suweni (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
The Community Service Program (KKN) is a form of student community engagement through the practical application of academic knowledge to address real societal needs. This program was carried out in Singapadu Tengah Village, specifically in Banjar Abasan, with the primary goal of enhancing environmental awareness and optimizing the use of local resources. Several work programs were implemented, including the distribution of fish seeds to support local livelihoods, the installation of informational signs in the beji area around the temple to maintain its sanctity, the placement of drinking water signs, and the installation of posters prohibiting littering to encourage responsible behavior. In addition, an innovative approach was introduced by creating a plastic waste fence using nets as a simple yet effective waste management solution. The methods applied in this program included direct observation, community outreach, and hands-on practice involving local residents. The outcomes indicated a noticeable increase in public awareness regarding environmental cleanliness, along with the development of creative, community-based solutions for managing plastic waste. Overall, this program is expected to be sustainable and provide long-term positive impacts on the community’s environmental practices and quality of life.